The Contribution of Attention to the Mere Exposure Effect for Parts of Advertising Images - Yagi, Yoshihiko; Inoue, Kazuya (Frontiers in Psychology, 2018)
Repeatedly presented stimuli are affectively evaluated more positively than novel stimuli. This phenomenon, known as the mere exposure effect, is used in advertising. However, it is still unclear in which part of advertising images the mere exposure effect occurs. Given the recent suggestion that attention plays an important role in the mere exposure effect, it is possible that the mere exposure effect does not occur for commercial products when advertising images consist of a commercial product along with an attractive human model. To investigate this possibility, we manipulated the relationship between advertising images repeatedly presented in an exposure phase and images presented in a later rating phase. In the exposure phase, participants were repeatedly presented with advertising images consisting of a cosmetic product along with an attractive female model and were instructed to attend to a specified part of the image (Experiment 4) or were given no such an instruction (Experiments 1, 2, and 3). In the rating phase, participants were asked to evaluate their preference for complete advertising images (Experiment 1), the images of female models (Experiment 2), or images of products (Experiments 3 and 4) that were previously presented or not presented. The mere exposure effect was found for whole advertising images and images of female models. On the other hand, the mere exposure effect for the images of products was seen only when participants were explicitly encouraged to direct their attention to the product parts of the advertising image. That is, the results of this study suggest that the mere exposure effect does not always occur for every part of the repeated advertising images, and that attention would modulate the mere exposure effect for advertising images.